Microplastics, invasive species and fungal stressors modulate antioxidative mechanisms, rhizosphere enzymes and microbial dynamics in alfalfa - Muhammad Anas; Muhammad Riaz; Meng-Ting Yan; Yi-Fan Liu; Ying Li; Shan- Shan Qi; Zhi-Cong Dai; Dao-Lin Du (Plant Stress)
Microplastics, invasive species, and fungal pathogens increasingly threaten the sustainability of artificial grasslands. Their combined impact on alfalfa-based grassland remains poorly understood. This study assessed the individual and interactive impacts of microplastics, Solidago canadensis, and Rhizoctonia solani on growth, antioxidative mechanism, soil enzyme dynamics, and rhizospheric microbial communities. This experiment comprised of 4 alfalfa seedlings/pot, with/without amendments of 1 % (w/w) microplastic/pot, application of R. solani and single seedling/pot of S. canadensis, both individually or in combination. Solidago canadensis significantly reduced plant height, leaf area and biomass by 57 %, 48 %, and 72 % respectively. Root biomass was more vulnerable than shoot biomass, decreasing by 81 %, 76 %, and 78 % due to microplastics, S. canadensis invasion, and R. solani, respectively. While catalase activity was higher in leaves, and that of peroxidase was greater in roots. However, activities of β-N-acetylglucosaminidase and β-Glucosidase increased by 80 % and 70 % respectively, under S. canadensis invasion, indicating intensified microbial processes. Sequencing of 16S rRNA yielded 1,280,487 reads, clustered into 17,500 amplicon sequence variants with 122 common unique features, and maximum 3,670 unique features were observed under microplastics. The relative abundance of top bacterial genera (Limnobacter, Sphingomonas, Lysobacter, and Saccharimonadales) was observed, and Chao1 and ACE indices were 683.37 and 682.33 for microplastics, respectively. PCoA explained 44.61 % of total variation across PC1 and PC2, clearly separating treatments. Network correlation showed significant microbial associations shaped by stressors. These results demonstrate that microplastics, invasion, and pathogenic fungi significantly reduce alfalfa performance, alter rhizospheric enzymatic profiles, and reshape microbial community structures. Their interactions may threaten functionality and resilience of grassland ecosystems, underscoring the need for integrated strategies to mitigate multiple soil-based stressors.